PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK MEBEL DI CV KUNTENG GARUDA SAKTI KECAMATAN TAMPAN PEKANBARU - Hendra Hadi Kusuma; Suarman Suarman; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of price on the purchase decision of furniture products in CV Kunteng Garuda Sakti subdistrict Tampan Pekanbaru. The population in this researc are all consumers who made purchasing decisions during the last 3 years ie 2015, 2016, 2017 with the number of consumers 532 people, and the sample of 84 people with sampling technique using the method of Proportional Random Sampling is a sampling technique performed by taking representative of each unit excist in the population. The data is measured by using The data analysis used is simple linear regression. The result of the descriptive research shows the price variable on the average of dominant consumers stated the price determined by CV Kunteng in accordance with product quality on the strength or durable of each of its products. While the variable purchase decisions on average consumers declare purchasing decisions made on CV Kunteng in because of a sense of need in furniture products in CV Kunteng. Based on these results, the hypothesis that has been done about the influence of price on the purchase decision of furniture products in CV Kunteng Garuda Sakti Tampan Pekanbaru District, it can be concluded that there is a significant influence on the purchase price of furniture products in CV Kunteng Pekanbaru by 49.1%, while the remaining 50.9% is influenced by other variables not examined in this study. Based on this result is expected CV Kunteng to always always pay attention to the price factor through affordability of the price among the community on every product that consumers want in an effort to improve consumer purchasing decisions.Keywords: Price, Decision, Purchase, Product, Furniture